2022
DOI: 10.1177/10497323221110109
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Female IBS Patients Concerning Physical Activity as Treatment Modality: A Qualitative Study

Abstract: The purpose of this study is to investigate the patient’s perspective on physical activity as treatment modality for irritable bowel syndrome (IBS). An interpretive phenomenological analysis (IPA) approach was used to examine the experiences of IBS patients with physical activity, through in-depth interviews with 11 female IBS patients. Experiences with physical activity varied substantially among patients. Patients attributed negative experiences with physical activity to embarrassment, anxiety, inability, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Previous research have indicated that IBS is related to physical factors [20][21][22][23][24] . Patients with IBS who engage in more physical activity see a reduction in GI symptoms, most likely as a result of an increase in intestinal transit and the absorptive capacity of the gut 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research have indicated that IBS is related to physical factors [20][21][22][23][24] . Patients with IBS who engage in more physical activity see a reduction in GI symptoms, most likely as a result of an increase in intestinal transit and the absorptive capacity of the gut 25 .…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the treatment, the total score changed from moderate to mild, representing a 38.9% reduction. It is worth noting that GI symptoms may hinder IBS patients, despite their motivation to engage in PA [ 42 , 43 ], underscoring the importance of selecting patients with mild to moderate symptoms to ensure better adherence to the activity.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with IBS are three times more likely to experience anxiety or depression than normal individuals [40], with a higher prevalence of these conditions in patients with IBS-constipation than the other IBS subtypes [17,18]. Besides, anxiety or depression can aggravate IBS GI and extra-GI symptoms by modulating visceral sensation and gut microenvironment and impacting the microbiome-gut-brain axis, ultimately reducing the QoL [40][41][42]. These findings posit the prime role of IBS psychological therapies, such as mindfulness behavioral therapy, hypnotherapy, multicomponent psychotherapy, relaxation therapy, and psychodynamic therapy [43][44][45].…”
Section: Psychological Interactions Between Exercise and Irritable Bo...mentioning
confidence: 99%
“…Physically inactive persons are 3.5 times more likely to suffer from IBS symptoms compared to physically active persons [49]. Increasing physical activity is viewed as one of the initial management strategies for preventing chronic morbidities, enhancing GI and psychological health, and improving overall IBS symptoms, including GI and extra-GI symptoms, such as fatigue, depression, anxiety, and stress [16][17][18]25,47], especially in IBS-C patients [17,18,42,50]. Even though physical activity positively affects physiological, physical, and psychological factors in IBS patients, the exact mechanisms until now are not well understood, and the evidence is still insufficient and inconclusive [12-Health, sport, rehabilitation Health, sport, rehabilitation Здоров'я, спорт, реабілітація Здоров'я, спорт, реабілітація Здоровье, спорт, реабилитация Здоровье, спорт, реабилитация 2023 9(4) 99 20,26,42].…”
Section: Do Physical Exercises Impact Irritable Bowel Syndrome and How?mentioning
confidence: 99%
See 1 more Smart Citation